Hubungan Pelaksanaan Peraturan Penilaian Angka Kredit Bidang Penelitian dan Semangat Kerja Dosen PTN - Soerjani Soerjani (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
The implementation of the credit-point regulation on research activities influences the morale of lecturers of state universities in East Java. This is a correlational and ex-post facto study. The data were collected by means of questionnaire and interview to 361 out of 5616 lecturers of state universities in East Java. The results show that the lecturers relate their teaching, research, and community-service activities to research with sufficiently high morale. Though complicated, the implementation procedures are suited with the condition of the university. There is no fixed schedule as to carrying out the research activities. The administrative management is found to be efficient and effective. There is no significant correlation between the implementation of credit-point regulation on research activities and the morale of state university lecturers in East Java.